Exploration of organizational practices that foster experiences of inclusion - de Largy, Christine (Cranfield University, 2023)
The literature on inclusion is growing, yet there remains a lack of clarity about how to foster an inclusive organization, with little attention paid to organizational inclusion practices or how inclusion is experienced. This thesis addresses these shortcomings through three studies. First, a systematic literature review reveals the inclusive organization tends to be studied through leadership, climate, workgroups, perceptions and practices; these elements may act generatively and interact to foster inclusion. Inclusion, conceptualised as treatment that satisfies needs for belongingness and uniqueness, but with less exploration of individual experiences of inclusion. Also, inclusion practices, although recognised as important in fostering an inclusive organization, lack empirical exploration. The second paper addresses this shortcoming; an empirical study with 15 Diversity and Inclusion Directors/Leads, using semi-structured interviews and thematic analysis. Findings indicate that practices may facilitate belonging and value uniqueness but organizations tend to prioritise practices which promote belonging. Practices that promote well-being and career development foster inclusion but are dependent upon the leaders involved. The third study is an empirical investigation of individual experiences of inclusion, with semi-structured interviews with 36 junior women. The study finds that employees prioritise being valued for their professional expertise and when treated as an individual, through well-being and career development practices. Interactions with line managers are the primary context for inclusion, although experiences of inclusion are complex and changeable. Overall theoretical contributions are that inclusion practices are inexact, practices may promote either belonging, or being valued, or both. Well- being and career development practices are re-positioned in the inclusive workplace model as inputs of inclusion. The study provides empirical evidence that employees prioritise task-related inclusion, with line managers as the primary context for inclusion, within day-to-day interactions.
Anderson, Deirdre - Associate Supervisor
Keywords: Diversity and inclusion; inclusion practices; workgroup inclusion; workplace inclusion; organizational inclusion; inclusive leadership; inclusion climate; experiences of inclusion